2020
DOI: 10.1126/sciadv.aba1715
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural diversification promotes multiple ecosystem services without compromising yield

Abstract: Enhancing biodiversity in cropping systems is suggested to promote ecosystem services, thereby reducing dependency on agronomic inputs while maintaining high crop yields. We assess the impact of several diversification practices in cropping systems on above- and belowground biodiversity and ecosystem services by reviewing 98 meta-analyses and performing a second-order meta-analysis based on 5160 original studies comprising 41,946 comparisons between diversified and simplified practices. Overall, diversificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
391
2
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 594 publications
(423 citation statements)
references
References 40 publications
22
391
2
8
Order By: Relevance
“…The identification of locally adapted sustainable farming practices (e.g. diversification of crop varieties, switch to perennial crops) might promote the biocontrol of both native habitat generalists and exotic pests [50][51][52]. As the threat of exotic species invasions is expected to increase with the intensification of international trade in the next decades [53,54], there is an urgent need to prevent or reduce establishment of new invaders and to develop innovative plant protection strategies for the control of emerging pests released from their coevolved antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of locally adapted sustainable farming practices (e.g. diversification of crop varieties, switch to perennial crops) might promote the biocontrol of both native habitat generalists and exotic pests [50][51][52]. As the threat of exotic species invasions is expected to increase with the intensification of international trade in the next decades [53,54], there is an urgent need to prevent or reduce establishment of new invaders and to develop innovative plant protection strategies for the control of emerging pests released from their coevolved antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…Relying on only a handful crops and on the enormous advances in plant breeding to feed the global population has greatly improved (global) food security, but has also contributed to malnutrition and has left farmers vulnerable to climate change. A meta-analysis of over 5000 original studies led Tamburini et al [43] to the conclusion that agricultural "diversification enhances biodiversity, pollination, pest control, nutrient cycling, soil fertility, and water regulation without compromising crop yields". Multispecies cropping systems constitute practical applications of ecological principles based on biodiversity, plant interactions, and other natural regulation mechanisms [44], and may lead to higher productivity, yield stability, ecological sustainability, and resilience to disruptions caused by climate change and other natural events.…”
Section: Agricultural Diversificationmentioning
confidence: 99%
“…In those cases where wild plants are better defended than domesticated plants, it is likely that at the landscape scale, herbivores would prefer crop-host over non-crop-hosts, this way reducing herbivore pressure on the wild plants. Additionally, pest control methods ranging from intercropping ( Tamburini et al, 2020 ) to the use of pesticides in cultivated crops could decrease the overall abundance of herbivores, leading to reduced herbivory in adjacent wild relatives. A long term, broad scale study in China found that the increased spatial and temporal use of Bt cotton did not just reduce the pest pressure of cotton bollworm ( Helicoverpa armigera ) on cotton, but also on other crops such as corn, peanuts and other vegetables attacked by this pest ( Wu et al, 2008 ).…”
Section: Land Use Change Affects Plant Direct Defenses Mediated By Hmentioning
confidence: 99%